Disruption of Dorsolateral But Not Ventrolateral Prefrontal Cortex Improves Unconscious Perceptual Memories - Lee, Taraz G. (Society for Neuroscience, 2013)
Attentive encoding often leads to more accurate responses in recognition memory tests. However, previous studies have described conditions under which taxing explicit memory resources by attentional distraction improved perceptual recognition memory without awareness. These findings lead to the hypothesis that explicit memory processes mediated by the prefrontal cortex (PFC) can interfere with memory processes necessary for implicit recognition memory. The present study directly tested this hypothesis by applying transcranial magnetic stimulation separately over either dorsolateral (DLPFC) or ventrolateral PFC (VLPFC) in humans before performance of a visual memory task. Disruption of DLPFC function led to improvement in recognition accuracy only in responses in which the participant's awareness of memory retrieval was absent. However, disruption of VLPFC function led to subtle shifts in recollection and familiarity accuracy. We conclude that explicit memory processes mediated by the DLPFC can indirectly interfere with implicit recognition memory.